1988
DOI: 10.1200/jco.1988.6.6.983
|View full text |Cite
|
Sign up to set email alerts
|

The impact of aggressive debulking surgery and cisplatin-based chemotherapy on progression-free survival in stage III and IV ovarian carcinoma.

Abstract: Forty consecutive patients with stage III and IV invasive ovarian carcinoma were treated on a phase II protocol consisting of optimal debulking surgery, induction cisplatin, cisplatin, doxorubicin, and cyclophosphamide (PAC) chemotherapy, 6-month interval laparoscopy, reinduction cisplatin, PAC chemotherapy, and second-look procedure. All 40 patients have either disease progression or have completed the 12-month protocol. Eighty-seven percent of the patients (35) underwent optimal (less than or equal to 2 cm r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(51 citation statements)
references
References 14 publications
1
49
0
1
Order By: Relevance
“…The prognostic value of complete tumour debulking on the overall survival has been demonstrated in many retrospective analyses (Piver et al, 1988;Covens, 2000;Bristow et al, 2002). On the basis of a recent meta-analysis of 81 cohorts of patients with stage III -IV disease, it was found that for each 10% increase in maximal cytoreduction, there was an associated 5.5% increase in median survival (Bristow et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of complete tumour debulking on the overall survival has been demonstrated in many retrospective analyses (Piver et al, 1988;Covens, 2000;Bristow et al, 2002). On the basis of a recent meta-analysis of 81 cohorts of patients with stage III -IV disease, it was found that for each 10% increase in maximal cytoreduction, there was an associated 5.5% increase in median survival (Bristow et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7]24,25 For this reason, increasingly radical surgery has been advocated in recent years to eliminate as much residual tumor as possible. 26 The use of rectosigmoid colon resection in the surgical management of patients with advanced ovarian carcinoma with bulky pelvic disease is rational, because the distal sigmoid frequently is involved by direct extension or serosal implantation from epithelial ovarian carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…We completely agree that chemotherapy and the extent of surgical therapy are important prognostic factors in ovarian carcinoma that have been identified by several meta-analyses. [2][3][4][5] Based on these results, platinumbased chemotherapy as well as optimal surgical debulking are now established therapeutic strategies for treatment of ovarian carcinoma.…”
Section: The Function Of Cox-2 In Human Ovarian Carcinomamentioning
confidence: 99%
“…[2][3][4][5] Thus, the therapeutic concept of extensive surgical de-bulking is relevant only for therapy of advanced ovarian carcinoma. Since we included 30% of patients with stage I or II ovarian carcinomas in our study, cytoreductive therapy could not be separately assessed as an independent factor in multivariate analysis for the whole study sample.…”
Section: The Function Of Cox-2 In Human Ovarian Carcinomamentioning
confidence: 99%
See 1 more Smart Citation